Nonheme oxoiron(IV) complexes of pentadentate N5 ligands: spectroscopy, electrochemistry, and oxidative reactivity - Wang, Dong; Ray, Kallol; Collins, Michael J.; Farquhar, Erik R.; Frisch, Jonathan R.; Gómez, Laura; Jackson, Timothy A.; Kerscher, Marion; Waleska, Arkadius; Comba, Peter; Costas, Miquel; Que, Lawrence (Chemical science, 2013)
Oxoiron(IV) species have been found to act as the oxidants in the catalytic cycles of several mononuclear nonheme iron enzymes that activate dioxygen. To gain insight into the factors that govern the oxidative reactivity of such complexes, a series of five synthetic S = 1 [FeIV(O)(LN5)]2+ complexes has been characterized with respect to their spectroscopic and electrochemical properties as well as their relative abilities to carry out oxo transfer and hydrogen atom abstraction. The FeO units in these five complexes are supported by neutral pentadentate ligands having a combination of pyridine and tertiary amine donors but with different ligand frameworks. Characterization of the five complexes by X-ray absorption spectroscopy reveals FeO bonds of ca. 1.65 Å in length that give rise to the intense 1s → 3d pre-edge features indicative of iron centers with substantial deviation from centrosymmetry. Resonance Raman studies show that the five complexes exhibit ν(FeO) modes at 825-841 cm−1. Spectropotentiometric experiments in acetonitrile with 0.1 M water reveal that the supporting pentadentate ligands modulate the E1/2(IV/III) redox potentials with values ranging from 0.83 to 1.23 V vs. Fc, providing the first electrochemical determination of the E1/2(IV/III) redox potentials for a series of oxoiron(IV) complexes. The 0.4 V difference in potential may arise from differences in the relative number of pyridine and tertiary amine donors on the LN5 ligand and in the orientations of the pyridine donors relative to the FeO bond that are enforced by the ligand architecture. The rates of oxo-atom transfer (OAT) to thioanisole correlate linearly with the increase in the redox potentials, reflecting the relative electrophilicities of the oxoiron(IV) units. However this linear relationship does not extend to the rates of hydrogen-atom transfer (HAT) from 1,3-cyclohexadiene (CHD), 9,10-dihydroanthracene (DHA), and benzyl alcohol, suggesting that the HAT reactions are not governed by thermodynamics alone. This study represents the first investigation to compare the electrochemical and oxidative properties of a series of S = 1 FeIVO complexes with different ligand frameworks and sheds some light on the complexities of the reactivity of the oxoiron(IV) unit.